2017
DOI: 10.1063/1.4989567
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of OH(A2Σ+) + H2: Electronic quenching, rotational energy transfer, and collisional depolarization

Abstract: Zeeman quantum beat spectroscopy has been used to determine the thermal (300 K) rate constants for electronic quenching, rotational energy transfer, and collisional depolarization of OH(AΣ) by H. Cross sections for both the collisional disorientation and collisional disalignment of the angular momentum in the OH(AΣ) radical are reported. The experimental results for OH(AΣ) + H are compared to previous work on the OH(AΣ) + He and Ar systems. Further comparisons are also made to the OH(AΣ) + Kr system, which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 45 publications
8
12
0
Order By: Relevance
“…As discussed in the next section, we attribute the experiment–theory discrepancy to the large yield of the adiabatic elastic and inelastic channel (channel 3), which was neglected in the previous analysis of the branching ratio 28 . To this respect, the recent work of Brouard et al 34 indicated that the inelastic scattering cross section is three times as large as the quenching one (channel 1 + channel 2) for the ground rotational state of the OH(A) reactant ( N OH = 0), confirming our results.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…As discussed in the next section, we attribute the experiment–theory discrepancy to the large yield of the adiabatic elastic and inelastic channel (channel 3), which was neglected in the previous analysis of the branching ratio 28 . To this respect, the recent work of Brouard et al 34 indicated that the inelastic scattering cross section is three times as large as the quenching one (channel 1 + channel 2) for the ground rotational state of the OH(A) reactant ( N OH = 0), confirming our results.…”
Section: Resultssupporting
confidence: 92%
“…Importantly, this particular steric approach has a large cone of acceptance leading to the large yield for channel 3 shown in Table 1 , although the dominance of this elastic and inelastic channel is weakened at higher energies. The adiabatic elastic and inelastic channel has been shown by Brouard et al to be quite dominant 34 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations